2012
DOI: 10.1071/sr11232
|View full text |Cite
|
Sign up to set email alerts
|

Boron in humus and inorganic components of Hamra and Grumosol soils irrigated with reclaimed wastewater

Abstract: The role of organic matter in soil boron (B) turnover and availability is not well understood. The forms and mobility of B are of special concern in soils irrigated with reclaimed wastewaters (RWW). We studied B distribution and binding in major components of two irrigated Mediterranean soils, with special emphasis on humus and water-mobile phases. The results showed that most B in the sandy loam Hamra soil and a large part in the clayey calcareous Grumosol was bound to extractable humus fractions and, in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 62 publications
0
3
0
Order By: Relevance
“…122 In arid and semiarid areas, B toxicity is a result of high levels of B in soils due to high evaporation rate together with additions of B via irrigation water. 43,45,119,125 In the mean time, Hingston 126 and Yermiyahu et al 127 reported higher sorption of B on soil organic matter than on clay; at similar pH levels and B concentration, the sorption was one to two orders of magnitude higher than on clays. In addition, human pollution may increase soil B to levels that are toxic for plants.…”
Section: Soilmentioning
confidence: 99%
See 2 more Smart Citations
“…122 In arid and semiarid areas, B toxicity is a result of high levels of B in soils due to high evaporation rate together with additions of B via irrigation water. 43,45,119,125 In the mean time, Hingston 126 and Yermiyahu et al 127 reported higher sorption of B on soil organic matter than on clay; at similar pH levels and B concentration, the sorption was one to two orders of magnitude higher than on clays. In addition, human pollution may increase soil B to levels that are toxic for plants.…”
Section: Soilmentioning
confidence: 99%
“…Temporary deficiency of available B can be triggered by liming of acid soils due to increased B adsorption at higher soil pH. 43 Furthermore, in soil, there are plenty of B-binding agents besides hydroxyl anions from dissociated water molecules. 123 The highest naturally occurring concentrations of soil B are in soils derived from marine evaporates and marine argillaceous sediments.…”
Section: Soilmentioning
confidence: 99%
See 1 more Smart Citation